2008
DOI: 10.4103/0255-0857.43575
|View full text |Cite
|
Sign up to set email alerts
|

The utility of IS6110 sequence based polymerase chain reaction in comparison to conventional methods in the diagnosis of extra-pulmonary tuberculosis

Abstract: IS6110 sequence based polymerase chain reaction (PCR) was compared with conventional bacteriological techniques in the laboratory diagnosis of extra-pulmonary tuberculosis (EPTB). One hundred and ninety one non-repeated clinical samples of EPTB and 17 samples from non-tuberculous cases as controls were included. All the samples were processed for Ziehl-Neelsen staining for acid fast bacilli (AFB) and 143 samples were processed by culture for M. tuberculosis. All the samples were processed for PCR ampliÞ cation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
1
7

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 7 publications
5
28
1
7
Order By: Relevance
“…Our results were in accordance with the results of several workers B Sekar et al 12 , Mandir verma et al 13 , Parmeet Kumar et al 14 who have reported similar sensitivity and specificity of PCR in detecting extra pulmonary tuberculosis.…”
Section: Extrapulmonary Tbsupporting
confidence: 93%
“…Our results were in accordance with the results of several workers B Sekar et al 12 , Mandir verma et al 13 , Parmeet Kumar et al 14 who have reported similar sensitivity and specificity of PCR in detecting extra pulmonary tuberculosis.…”
Section: Extrapulmonary Tbsupporting
confidence: 93%
“…Whenever it was properly executed, PCR has proved to be a very sensitive test in EPTB [9][10][11][12]. In the present study, PCR could detect M. tuberculosis in 11% of the tested cases.…”
Section: Discussionmentioning
confidence: 50%
“…Sekar et al(2008) 21 reported that sensitivity of PCR was 90% in their study. Different studies showed sensitivity ranged between 20% and 94% for PCR assay of extra-pulmonary specimens 22,23 .…”
Section: Discussionmentioning
confidence: 90%